FQSPM-SWOT for strategic alliance planning and partner selection; case study in a holding car manufacturer company - Akhavan, Peyman; Barak, Sasan; Maghsoudlou, Hamidreza; Antuchevičienė, Jurgita (Technological and Economic Development of Economy, 2015)
In today’s competitive environment, holding companies are usually unable to successfully compete in production of goods and services due to technological sophistication. Therefore, for success of holding companies, selecting appropriate strategic alliance partner is a critical factor. Accordingly, the aim of the paper is to propose a systematic approach for an effective partner selection. Firstly, the underlying motivation and reasons for a strategic alliance building are presented using a SWOT analysis. Criteria of partners’ evaluation are attained on the basis of combining strengths, weaknesses, opportunities and threats. Due to uncertainty of criteria, they are weighted using fuzzy quantitative strategic planning matrix (FQSPM). Because of a large number of criteria obtained from the SWOT-FQSPM analysis, criteria are diminished based on their weights using the Gap analysis with fuzzy data ranking. In the next step, it is proposed to apply four ranking algorithms including the Fuzzy Additive Ratio Assessment (ARAS-F), the Fuzzy Complex Proportional Assessment (COPRAS-F), the Fuzzy Multi-Objective Optimization by Ratio Analysis (Fuzzy MOORA), and the Fuzzy Technique for Order Preference by Similarity to Ideal solution (Fuzzy TOPSIS) to evaluate strategic partners. Finally, the results are combined with the help of the Borda method to choose the best alternative. To illustrate the efficiency of the proposed approach, a real partner selection problem at a holding industries factory in Iran is presented.